Outcomes of Management of Intestinal Obstruction at an Urban Tertiary Hospital in Sub Saharan Africa: a cross‑sectional study - Nakanwagi, Arlene Muzira; Kijjambu, Stephen C.; Ongom, Peter; Luggya, Tonny Stone (BMC surgery, 2021)
Intestinal obstruction (IO) is a common cause of acute abdomen globally, it remains challenging as it increases surgical financial expenditure while also causing major morbidity. Clinically it presents with nausea, vomiting, colicky abdominal pain and cessation of bowel movements or passage flatus and stool. Diagnosis, especially in resource limited settings, can be clinical but is usually confirmed radiologically. We studied the current diagnosis, management and outcomes of IO in Mulago Hospital. This was a prospective study done at all the surgical units of Mulago from January to May 2014 to assess general diagnosis and management of IO. Ethical approval was got in line with Helsinki declaration, we used pretested and validated questionnaires to collect data. Informed consent was got with eligible and consenting/assenting patients that fitted the inclusion criteria of age and presenting with suspected intestinal obstruction. Uni-variate and bi-variate variables analysis was done plus measures of association. We enrolled 135 patients, excluded 25 and recruited 110 patient. We had more males than females i.e. 71.8% males and 28.2% females. Colicky abdominal pain, abdominal distension, and vomiting were commonest symptoms, then abdominal distension, increased bowel sounds and abdominal tenderness were the commonest signs. Most patients’ (51%) were diagnosed radiologically with a lesser number clinically diagnosed. “Dilated bowel loops” was the commonest radiological sign. Surgery was the main stay of management at 72.7% while 27.3% were conservatively managed. Postoperatively the bowels opened averagely on the 3rd post-operative day (POD) with return of bowel sounds occurring on 5th POD. Most discharges (73%) occurred by the 7th POD. Unfavourable outcomes were prolonged hospital stay followed by wound sepsis (surgical site infection) and then Mortality. This study noted that In Mulago we mostly diagnosed patients radiologically with most surgically managed and which is similar to regional practices. Postoperatively bowel opening happening on third POD with return of bowel sounds on fifth POD. Prolonged hospital stay followed by wound sepsis and then mortality were commonest unfavorable management outcomes.